Cover Image. Issue 12 (12th December 2018) - Gautam, Swarnima Singh; Singh, Vrijendra
Abstract : The cover image is based on the Research Article The state‐of‐the‐art in software development effort estimation, by Swarnima Singh Gautam, Vrijendra Singh, https://doi.org/10.1002/smr.1983 .